Factory man : how one furniture maker battled offshoring, stayed local-- and helped save an American town - Macy, Beth (Little, Brown and Company, 2014)
Describes how the chairman of Vaughan-Bassett Furniture fought for his more than seven hundred employees in a small Virginia town using legal maneuvers, factory efficiencies, and his wits and determination in the wake of sales losses to cheap Asian furniture imports.